2017
DOI: 10.1038/ismej.2016.195
|View full text |Cite
|
Sign up to set email alerts
|

Cheating fosters species co-existence in well-mixed bacterial communities

Abstract: Explaining the enormous biodiversity observed in bacterial communities is challenging because ecological theory predicts that competition between species occupying the same niche should lead to the exclusion of less competitive community members. Competitive exclusion should be particularly strong when species compete for a single limiting resource or live in unstructured habitats that offer no refuge for weaker competitors. Here, we describe the 'cheating effect', a form of intra-specific competition that can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 63 publications
1
82
0
Order By: Relevance
“…Shaking is supposed to increase the mixing of cells and public goods, and has been shown to improve pyoverdine cheating abilities in P. aeruginosa (Leinweber et al. ). We found the opposite to be the case for the Burkholderia siderophores (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shaking is supposed to increase the mixing of cells and public goods, and has been shown to improve pyoverdine cheating abilities in P. aeruginosa (Leinweber et al. ). We found the opposite to be the case for the Burkholderia siderophores (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…), and that cheaters perform best in shaken cultures (Leinweber et al. ), at high cell density (Ross‐Gillespie et al. ) and when rare (Ross‐Gillespie et al.…”
Section: Discussionmentioning
confidence: 99%
“…These levels of iron supplementation have previously been shown to either reduce pyoverdine production to intermediate levels (1 μM FeCl 3 ) or to completely stall pyoverdine synthesis (40 μM FeCl 3 ) [14]. Furthermore, competition experiments between PAO1 cooperators and their cheating isogenic knock-out mutant (PAO1 ΔpvdD ΔpchEF), deficient for siderophore production, revealed that cheats could only invade without the supplementation of extra iron [13].…”
Section: Strains and Growth Conditionsmentioning
confidence: 99%
“…Previous work revealed that increased spatial structure maintains cooperation because it reduces pyoverdine diffusion and cell dispersal. In other words, spatial structure ensures that pyoverdine sharing occurs predominantly among producer cells [13,[18][19][20]. The second factor involves the relative costs and benefits of pyoverdine production [14,17].…”
Section: Introductionmentioning
confidence: 99%
“…; Leinweber et al. ). In intraspecific competition, the secreted siderophores can be shared as public goods between cells that possess a compatible receptor for uptake.…”
mentioning
confidence: 97%